ANALISIS PELAKSANAAN PELATIHAN KARYAWAN PADA CV. MATA AIR MOTOR JAMBI - Eko Suharsono (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2014)
The purpose of this study is to obtain an overview of the implementation of employee training at CV. Mata Air Motor Jambi as well as to analyze the implementation of employee training at CV. Jambi Motor Springs. The method used in this study is to use survey methods, namely to measure attitudes, opinions and perceptions of a person or group of social phenomena. The variables to be measured are translated into research variable indicators. Then these indicators are used as a starting point for compiling instrument items which can be in the form of statements or questions. The method is to give the value of each question given in a list of questions or questionnaires and then get the results of the training variables high employees, then the aspect with the highest need for training and the aspect with the lowest aspect is the selection of trainees. From the results described above, the focus that needs to be improved is the aspect of selecting employee training participants in order to get training participants who meet the requirements set by the company concerned.